Variants of the arachidonate 5-lipoxygenase-activating protein (ALOX5AP) gene and risk of ischemic stroke in Han Chinese of eastern China() - Wang, Gannan (Editorial Department of Journal of Biomedical Research, 2011)
Variants of the arachidonate 5-lipoxygenase-activating protein (ALOX5AP) gene have been suggested to play an important role in the pathogenesis of atherosclerosis and ischemic stroke. This study was aimed to explore the association of ALOX5AP variants with ischemic stroke risk in Han Chinese of eastern China. A total of 690 ischemic stroke cases and 767 controls were recruited. The subjects were further subtyped according to the Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria. On the basis of that, two polymorphisms of the ALOX5AP gene (rs10507391 and rs12429692) were determined by TaqMan genotyping assay. In addition, plasma leukotriene B4 (LTB4) levels were analyzed in these subjects. There was no evidence of association between the two variants of ALOX5AP and the risk of ischemic stroke or its TOAST-subtypes. Haplotype analysis and stratification analysis according to sex, age, body mass index, hypertension, and diabetes also showed negative association. Analysis of LTB4 levels in a subset of cases and controls revealed that LTB4 levels were significantly higher in ischemic stroke cases than in the controls (70.06±14.75 ng/L vs 57.34±10.93 ng/L; P = 0.000) and carriers of the T allele of the rs10507391 variant were associated with higher plasma LTB4 levels (P = 0.000). The present study suggests there is no association of the two polymorphisms in the ALOX5AP gene with ischemic stroke risk in Han Chinese of eastern China.